2020
DOI: 10.1101/2020.06.11.146175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced C/EBPs binding to C>T mismatches facilitates fixation of CpG mutations

Abstract: Knowledge of mechanisms responsible for mutagenesis of adult stem cells is crucial to track genomic alterations that may affect cell renovation and provoke malignant cell transformation. Mutations in regulatory regions are widely studied nowadays, though mostly in cancer. In this study, we decomposed the mutation signature of adult stem cells, mapped the corresponding mutations into transcription factor binding regions, and assessed mutation frequency in sequence motif occurrences. We found binding sites of C/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These cytosines belong to the core CG pair which is prone to spontaneous deamination. The produced mismatches are then protected from repair through enhanced CEBPB binding resulting in mutation fixation 34 . Such ASBs, on the one hand, confirm frequent mutagenesis of CEBPB binding sites, and, on the other hand, suggest the action of purifying selection that stabilizes such sites as heterozygous variants.…”
Section: Resultsmentioning
confidence: 99%
“…These cytosines belong to the core CG pair which is prone to spontaneous deamination. The produced mismatches are then protected from repair through enhanced CEBPB binding resulting in mutation fixation 34 . Such ASBs, on the one hand, confirm frequent mutagenesis of CEBPB binding sites, and, on the other hand, suggest the action of purifying selection that stabilizes such sites as heterozygous variants.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, they found that 5-methylcytosine at the CG site enhances binding of CEBPB. Enhanced binding of CEBPB with C>T mutations at base 5 of the motif was recently confirmed by Ershova et al (2020) Preprint .…”
Section: Resultsmentioning
confidence: 82%